2020
DOI: 10.1016/j.jtauto.2020.100048
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response to homologous epitopes of Epstein-Barr virus, Mycobacterium avium subsp. paratuberculosis and IRF5 in patients with different connective tissue diseases and in mouse model of antigen-induced arthritis

Abstract: Background Improved knowledge of different biomarkers is crucial for early diagnosis of rheumatic diseases and to provide important insights for clinical management. In this study, we evaluated the seroreactivity of patients with different connective tissue diseases (CTDs) (rheumatoid arthritis, RA; systemic lupus erythematosus, SLE; systemic sclerosis, SSc; and Sjogren’s syndrome, SSj) to interferon regulatory factor 5 (IRF5) peptide and homologs derived from Epstein-Barr virus (EBV) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
(45 reference statements)
0
14
0
Order By: Relevance
“…This discordance was also flagged in a recent study [ 28 ] wherein a group of household contacts who were negative for TST and IGRA had shown antibodies to MtM-associated antigens. In related studies [ 42 , 43 ], RA patients had also shown antibodies to mycobacterial proteins PknG, PtpA and MAP_4027. Though the authors had sourced these proteins from Mycobacterium avium subsp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This discordance was also flagged in a recent study [ 28 ] wherein a group of household contacts who were negative for TST and IGRA had shown antibodies to MtM-associated antigens. In related studies [ 42 , 43 ], RA patients had also shown antibodies to mycobacterial proteins PknG, PtpA and MAP_4027. Though the authors had sourced these proteins from Mycobacterium avium subsp.…”
Section: Discussionmentioning
confidence: 99%
“…RA patients harbour antibodies to a peptide epitope of MAP_4027 (this antigen is also present in Mtb) which cross-reacts with interferon regulatory factor 5 (IRF5). This structural mimicry could contribute to the pathogenesis of IMIDs by dysregulating the signalling by IRF5 which is a central regulator of inflammatory responses [ 43 , 54 ]. The regions of low TB prevalence (e.g., USA, Canada and Europe) show a high prevalence of MAP which could substitute for Mtb as an environmental trigger for IMIDs [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…That is especially relevant since PTB is a disease that affects not only cattle but also other domestic (sheep, goats) [59] and wild ruminants (deer, fallow-deer) [60,61], and other species like camelids [62], that have similar digestive characteristics although they are not true ruminants [63]. Improvement of the identification of MAP-infected animals through sensitive biomarker-based ELISAs could also help to study and confirm the potential role of MAP-infection as a common pathogenetic contributor to various autoimmune diseases [10].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MAP has a clear zoonotic potential since it has been postulated as a possible trigger factor in several autoimmune diseases in humans such as Crohn's disease (CD) [3,4], type I diabetes (T1D) [5], multiple sclerosis (MS) [6,7] or rheumatoid arthritis (RA) [8,9]. One mechanism that has been suggested to cause the onset and/or exacerbation of autoimmune disease is molecular mimicry, whereby MAP antigens share sequences or structural similarities with self-antigens [10], so the immune response against MAP antigens could also induced undesirable immune responses against host proteins in genetically predisposed individuals [11].…”
Section: Introductionmentioning
confidence: 99%
“…This discovery supports the hypothesis that IRF5 is a potential auto-immune target of RA. However, further studies in a larger group of patients are needed to further confirm these findings [ 60 ].…”
Section: Ra Immunopathogenesismentioning
confidence: 99%